Determinants of the fashion industry development : the cases of Italy and Spain - Hryhoryeva, Aliaksandra (2024)
Despite sharing close cultural and geographical ties, Italy and Spain have developed notably differently in the fashion industry. While in the two countries, both fast and luxury fashion have been developing and consumed, Italy is yet more linked to luxury fashion and has been associated with this fashion sector, while Spain is widely known for its consumer-accessible, fast fashion apparel. The different fashion development in both countries has also influenced the importance of fashion in their economies historically and in the current realm. This bachelor thesis aims to evaluate the importance of fashion in the economies of Spain and Italy based on the analysis of long-term historical and socio-economic development using the method of comparative analysis. It also evaluates the causes that predetermined the different fashion paths in the two examined countries.